2013
DOI: 10.1016/j.tcb.2013.06.005
|View full text |Cite
|
Sign up to set email alerts
|

IRE1: ER stress sensor and cell fate executor

Abstract: Cells operate a signaling network termed unfolded protein response (UPR) to monitor protein-folding capacity in the endoplasmic reticulum (ER). IRE1 is an ER transmembrane sensor that activates UPR to maintain ER and cellular function. While mammalian IRE1 promotes cell survive, it can initiate apoptosis via decay of anti-apoptotic microRNAs. Convergent and divergent IRE1 characteristics between plants and animals underscore its significance in cellular homeostasis. This review provides an updated scenario of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
418
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 473 publications
(424 citation statements)
references
References 90 publications
4
418
0
2
Order By: Relevance
“…However, little is known concerning the mechanism by which sorafenib induces cell death and the drug resistance gained in response to HCC treatment. Activation of the UPR by the IRE1 signaling pathway is a key component of cell survival decisions in response to ER stress (34). We observed the activation of IRE1 in the sorafenib-treated HCC cells, thereby indicating that sorafenib induces the UPR and ER stress-related apoptosis.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…However, little is known concerning the mechanism by which sorafenib induces cell death and the drug resistance gained in response to HCC treatment. Activation of the UPR by the IRE1 signaling pathway is a key component of cell survival decisions in response to ER stress (34). We observed the activation of IRE1 in the sorafenib-treated HCC cells, thereby indicating that sorafenib induces the UPR and ER stress-related apoptosis.…”
Section: Discussionmentioning
confidence: 57%
“…The IRE1 signaling pathway functions as a switch between cytoprotective and proapoptotic outcomes in response to ER stress, and the activation of IRE1 plays a crucial role in the UPR to enhance cell survival (34). Our results indicate that sorafenib treatment triggers the UPR and ER stress-related apoptosis in HCC cells, given the essential role of IRE1 activation in governing the switch from adaptive UPR to ER stress-associated apoptosis in sorafenib-treated HCC cells.…”
Section: Discussionmentioning
confidence: 63%
“…10,11 Intriguingly, AGB1 is involved in unfolded protein response (UPR), 12,13 a pathway in so-called endoplasmic reticulum (ER) quality control to cope with ER stresses. 14,15 . The molecular mechanism of ER quality control is evolutionarily well conserved among eukaryotic cells.…”
mentioning
confidence: 99%
“…The absence of detectable Ire1a in cells stimulated with LPS for 24 h indicates that misfolded proteins have probably not reached the threshold required for its induction. It is also possible that Ire1a levels are kept in check during early activation because it can decrease protein folding in the ER by promoting mRNA decay, and also induce apoptosis (30). We found that Hrd1 transcript and protein amounts were both higher in WT B cells than in CD40 2/2 B cells and that both were induced when WT B cells…”
Section: Discussionmentioning
confidence: 66%